PENINGKATAN HASIL BELAJAR MAHASISWA SEMESTER VI PGSD UNIVERSITAS KARIMUN PADA MATA KULIAH PEMBELAJARAN TEMATIK SD MENGGUNAKAN METODE MIND MAPPING - Desi Indriyani (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The purpose of this study was to improve student learning outcomes in elementary thematic learning subjects using the mind mapping method. The hypothesis of action research is that if the mind mapping method is used it can improve the learning outcomes of sixth semester students in elementary thematic learning subjects. This research is classroom action research. The design of this research is based on Kemmis and Taggart using a spiral system. Each cycle consists of planning, implementation, observation and reflection. The results of this study were seen from the increase in student learning outcomes in the first cycle, which was 70.80% and the increase in the second cycle changed to 90.25%. Based on the results of the observational analysis, there was an increase in the learning process, from 80% of the descriptors that were implemented to 95% of the descriptors that were implemented. Based on the data above, it can be concluded that the mind mapping method can improve student learning outcomes in elementary thematic learning subjects.